2010
DOI: 10.4315/0362-028x-73.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characterization, and Genotypic Analysis of Escherichia coli O157:H7/NM fromSelected Beef Exporting Abattoirs of Argentina

Abstract: In Argentina, Escherichia coli O157:H7/NM (STEC O157) is the prevalent serotype associated with hemolytic uremic syndrome (HUS), which is endemic in the country with more than 400 cases per year. In order to estimate the prevalence and characteristics of STEC O157 in beef cattle at slaughter, a survey of 1,622 fecal and carcass samples was conducted in nine beef exporting abattoirs from November 2006 to April 2008. A total of 54 samples were found positive for STEC O157, with an average prevalence of 4.1% in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 37 publications
6
28
1
2
Order By: Relevance
“…Consistent with previous studies (8,25), we also observed a significant difference in the motility of O157 from Argentina (predominantly motile strains) and Australia (predominantly nonmotile strains), further supporting potential differentiation of the O157 populations in each country.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies (8,25), we also observed a significant difference in the motility of O157 from Argentina (predominantly motile strains) and Australia (predominantly nonmotile strains), further supporting potential differentiation of the O157 populations in each country.…”
Section: Discussionsupporting
confidence: 92%
“…Fegan and Desmarchelier (8) tested 102 Australian E. coli O157 isolates from human and animal sources for the pres- (22,25). Isolates in the current study represented multiple genotypes in proportions similar to the diversity previously demonstrated in Argentina and Australia.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Aslam et al (2009) was successfully isolated E. coli bacteria from the slaughtering equipments and cow hide that have been skined. Masana et al (2010) reported that 54 samples of beef that come from the slaughterhouse in Argentina (slaughtering period of November 2006 up to April 2008) were containing E. coli bacteria. Ingham et al (2010) reported that beef has potential to get E. coli bacteria and non fecal coliform bacteria contamination Indonesia government's regulation on beef and carcass quality defined five strictly requirements as follows: TPC for a maximum 10 6 CFU/g, total coliform bacteria for a maximum 10 2 CFU/g, total E. coli bacteria up to 10 CFU/g, total S. aureus bacteria for a maximum of 10 2 CFU/g and zero tolerant for Salmonella bacteria per 25 g samples (SNI 3932, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cattle are main reservoir for STEC (2,20,26). Investigations carried out in different part of Europe, Asia, North America have showed that 10-80% cattle were infected with STEC (1,2,5,8,27,39).…”
Section: Discussionmentioning
confidence: 99%